A series-resonant DC - Chien-Ming Wang
A DC/AC inverter without cycloconversion configured by a half-bridge series-resonant inversion (HB-SRI) circuit is presented. The inverter is a series resonator with two auxiliary switches in shunt with the resonant capacitor so as to configure adaptively the output current suitable for impedance load. The output sinusoidal voltage is synthesized by a series of equal-amplitude quasisinusoidal pulses (QSPs) and the corresponding current is formed by unequal QSPs and adaptively phase-shifts to the impedance load. The presented HB-SRI is operated by frequency modulation with a constant-on time control. System modeling and waveform syntheses for the output sinusoidal voltage and its current are clearly derived, A typical design example of a 500 W HB-SRI inverter is examined to assess the system performance. The power efficiency is over 90% when the inverter output is above 200 W. The total harmonic distortions (THDs) for various impedance loads are all within 6%
Keywords: 500 W; Auxiliary switches; Constant-on time control; Equal-amplitude quasisinusoidal pulses; Frequency modulation; Half-bridge series-resonant inversion; Impedance-load drives; Output sinusoidal voltage; Performance; Power efficiency; Resonant capacitor; Series-resonant DC/AC inverter; System modeling; Total harmonic distortion; Waveform syntheses